2015
DOI: 10.1007/s13679-015-0180-9
|View full text |Cite
|
Sign up to set email alerts
|

Built Environments and Active Living in Rural and Remote Areas: a Review of the Literature

Abstract: Rural children and adults are more likely to have obesity than their urban counterparts even after adjustment for individual-level behaviors, suggesting that rural environments may promote obesity. The rural built environment may be an important area of research that can help us understand rural-urban disparities in obesity. The purpose of this review is to summarize the rural built environment and active living literature, and to address key issues, gaps, and observations in the field. A literature review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 85 publications
10
137
0
Order By: Relevance
“…8 This suggests that ciclovias in rural areas have a similar draw and potential to promote physical activity as in urban areas. In rural areas there are limited high quality accessible and affordable places for physical activity, such as parks, recreation centers, 5 and ciclovias could provide opportunities for rural residents to obtain physical activity by taking advantage of the existing resources of the streets and opening them up for physical activity. Participants who attended more than one ciclovia called Sunday Streets in San Francisco engaged in ≥20 minutes of physical activity compared with first time participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This suggests that ciclovias in rural areas have a similar draw and potential to promote physical activity as in urban areas. In rural areas there are limited high quality accessible and affordable places for physical activity, such as parks, recreation centers, 5 and ciclovias could provide opportunities for rural residents to obtain physical activity by taking advantage of the existing resources of the streets and opening them up for physical activity. Participants who attended more than one ciclovia called Sunday Streets in San Francisco engaged in ≥20 minutes of physical activity compared with first time participants.…”
Section: Discussionmentioning
confidence: 99%
“…4 This inactivity may in part be due to the lack of opportunities for physical activity and an infrastructure that is not conducive to walking and biking in rural communities. 5 …”
Section: Introductionmentioning
confidence: 99%
“…23 A literature review in 2015 identified very few studies that targeted rural areas, and of those studies, even fewer have targeted minority or indigenous populations. 24-26 …”
Section: Introductionmentioning
confidence: 99%
“…Adherence to recommended guidelines in the United States is generally low, but these PA‐related behavior patterns may vary by setting. Previous literature has indicated that rural communities, often defined as those in nonmetropolitan counties, may face unique challenges to engaging in PA associated with the built environment, such as less access to community resources including parks/green spaces, walkable destinations, and public transportation . Such barriers faced by rural communities may be compounded by differences in social factors, such as a lack of presence of physically active role models, increased caregiving duties, and less social support for engaging in PA …”
mentioning
confidence: 99%